Characteristics of anatomic injury of coronary arteries in patients with acute myocardial infarction without ST elevation depending on plasma level of gene 2 growth stimulating factor and risk of adverse even - V.P. Ivanov (Danylo Halytsky Lviv National Medical University, 2020)
Aim. Assessment of the character of anatomical coronary lesions in patients with acute myocardial infarction without ST elevation depending on plasma level of gene 2 growth stimulating factor (ST2), and risk of adverse events.